2009
DOI: 10.1002/mop.24206
|View full text |Cite
|
Sign up to set email alerts
|

Small‐size uniplanar coupled‐fed PIFA for 2.4/5.2/5.8 GHz WLAN operation in the laptop computer

Abstract: A coupled‐fed PIFA (printed inverted‐F antenna) printed on a small‐size FR4 substrate promising for 2.4/5.2/5.8 GHz WLAN (wireless local area network) operation in the laptop computer is presented. When mounted at the top edge of the system ground plane or supporting metal frame of the laptop display, the PIFA shows a height of 9 mm and a small width of 7 mm only. With a narrow width, it is promising for more internal antennas to be mounted along the top edge of the supporting metal frame of the laptop display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
(41 reference statements)
0
27
0
Order By: Relevance
“…However, near omnidirectional direction is observed in the azimuthal plane (x-y plane) of the two antennas. The average antenna gain in the azimuthal plane is also an important factor considered for practical laptop computer applications [4]. The measured average antenna gain in the azimuthal plane is defined as the antenna gain over all of the angles.…”
Section: Proposed Design Of Two Antennas With Improved Isolationmentioning
confidence: 99%
“…However, near omnidirectional direction is observed in the azimuthal plane (x-y plane) of the two antennas. The average antenna gain in the azimuthal plane is also an important factor considered for practical laptop computer applications [4]. The measured average antenna gain in the azimuthal plane is defined as the antenna gain over all of the angles.…”
Section: Proposed Design Of Two Antennas With Improved Isolationmentioning
confidence: 99%
“…However, it is noted that when mounted along the top edge of the system ground plane or supporting metal frame of the laptop display, most of these antennas [2][3][4][5][6][7][8][9][10][11][12] will occupy a length of about 20 mm or larger. Recently, it is demonstrated that by using the coupling feed [13,14] for the printed PIFA, different from the cases of using the traditional direct feed [3][4][5][6], the occupied length of the internal WLAN antenna along the top edge of the system ground plane can be greatly decreased to be about 13 mm or less. This is mainly because the coupling feed can introduce additional capacitive reactance to compensate for the large inductive reactance caused by the reduced size or length of the PIFA for achieving the desired quarter-wavelength mode excitation.…”
Section: Introductionmentioning
confidence: 99%
“…For the internal WLAN (wireless local area network) antenna, which has become a standard embedded element in the general laptop computers, many promising dual-band or triple-band designs to cover the 2.4/5.2/5.8 GHz bands (2400 -2484/5150 -5350/5725-5875 MHz) have been reported in the published papers [2][3][4][5][6][7][8][9][10][11][12][13][14]. These antennas include using the slot element [2], the direct-fed metalplate or printed PIFA (planar inverted-F antenna) [3][4][5][6], the monopole element [7][8][9][10][11][12], and the coupled-fed PIFA [13,14]. However, it is noted that when mounted along the top edge of the system ground plane or supporting metal frame of the laptop display, most of these antennas [2][3][4][5][6][7][8][9][10][11][12] will occupy a length of about 20 mm or larger.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, a universal serial bus (USB) dongle, a pint-size terminal that can be linked to a computer, has been developed as a wireless adapter designed to compensate for insufficient functions of laptops and other digital devices [1,2]. Many antennas have been proposed and designed, including monopole antennas [3][4][5][6], slot antennas [7][8][9], loop antennas [10,11], and planar inverted-F antennas (PIFA) [12][13][14][15][16], in consideration that a wireless USB dongle is easy to carry and has a multiplex function of plug-and play. As known, planar antennas that can be printed on a thin dielectric substrate are promising candidates for applications to thin-profile mobile devices including mobile handsets, laptop computers, navigators, etc.…”
Section: Introductionmentioning
confidence: 99%